Degradation of PTFE non-stick coatings for application in the food service industry. (September 2020) - Andreatta, Francesco; Lanzutti, Alex; Aneggi, Eleonora; Gagliardi, Andrea; Rondinella, Alfredo; Simonato, Michele; Fedrizzi, Lorenzo
Highlights: Mechanical wear and thermal ageing cause crazing in the PTFE-based coating. Coating ageing has been simulated and compared with life-tested components. Crazed areas show a significant loss of anti-stick properties. Microstructural changes lead to an increase of crystallinity in the composite matrix. Mechanical properties strongly decrease after ageing. Abstract: Polytetrafluoroethylene (PTFE) is an engineer polymer used for a wide range of applications, such as food heating and processing. Fluoro-based polymer coatings exhibit strong anti-stick properties but are often exposed to rather aggressive environments and severe operating conditions. Thermal ageing negatively influences the structure and crystallinity of PTFE while cleaning agents and mechanical wear further increase the degradation rates of such coatings. The following research investigates composite PTFE coatings behavior, both during service time and in simulated environment. Samples morphology and surface chemistry have been investigated by means of SEM and by EDXS, respectively. Other important information, such as the crystallinity and the phase transitions, have been instead evaluated through XRD, DSC and TGA. The composite coating showed to be susceptible to thermal ageing, exhibiting a strong decrease in mechanical properties and an increase in the amount of deposits adhered to the surface after contact frying.